Thomson scattering measurements in atmospheric plasma jets - Gregori, G; Schein, J; Schwendinger, P; Kortshagen, U; Heberlein, J; Pfender, E (1999)
Electron temperature and electron density in a dc plasma jet at atmospheric pressure have been obtained using Thomson laser scattering. Measurements performed at various scattering angles have revealed effects that are not accounted for by the standard scattering theory. Differences between the predicted and experimental results suggest that higher order corrections to the theory may be required, and that corrections to the form of the spectral density function may play an important role.